The Pattern of Electric Vehicle Demand among the Upper-middle Income Class in Indonesia - Tan, Pauline (Proceeding of International Conference on Entrepreneurship (IConEnt), 2023)
Electric vehicles have emerged as a very promising solution as awareness of the effects of fossil fuel vehicles on air pollution and climate change has increased. Electric vehicles are not only changing the way we move, but they are also changing many aspects of our lives, from the environment to the economy and public health.As of 2023, the global market size for electric vehicles has reached USD 388.1 billion and is expected to continue to grow to USD 951.9 billion by 2030 (Marketsandmarkets, 2023). With the increasing technology, environmental awareness, and government policies, electric vehicles are becoming a promising choice as a sustainable transportation. As consumers and industries become more aware of climate change and air pollution, they are starting to switch to electric vehicles to reduce carbon emissions. This has led to the growing electric vehicle market with innovation and investment around the world.